Effect of rosemary (Rosmarinus officinalis) extracts on the oxidative stability and sensory acceptability of soybean oil. (14th October 2014) - Dias, Liara S; Menis, Michele E C; Jorge, Neuza
Abstract BACKGROUND Plant extracts have been used as an alternative to the use of synthetic antioxidants in order to preserve oils from oxidative degradation. Additionally, these extracts add special flavors and aromas to the food. Thus, the objective of this study was to evaluate the effect of hydroethanolic extracts of fresh and freeze‐dried rosemary in the oxidative stability of soybean oil under accelerated storage in an oven. RESULTS The application of the extracts in the oil showed that that freeze‐dried extract was better in reducing the formation of oxidation products, showing 8.6 meq kg−1 of peroxides after 20 days of storage. On the other hand, the mixture of the natural extract with t‐butylhydroquinone conferred better oxidative stability index until the 20th day, 9.7 h. Both extracts prevented the loss of tocopherol, not differing between each other (P > 0.05), and present approximately 505 mg kg−1 of residual tocopherols. The sensory evaluation revealed that consumers accepted equally the oils added and not added of the rosemary extracts. CONCLUSION The extracts are therefore potential sources of natural antioxidants and they would be well accepted by consumers if applied by the food industry to replace synthetic antioxidants. © 2014 Society of Chemical Industry